A comparative survey of scheduling mechanisms in the internet - Miaji, Yaser; Hassan, Suhaidi (IEEE Computer Society, 2009)
As the Internet is rapidly growing and its popularity increases, users tend to use creative, timeconservative, entertained and economical technologies. Real-time applications such as online gaming, voice and video applications are becoming more popular. Research effort to improve scheduling mechanisms in routers is currently given less attention by network researchers. This trend is far behind in industrial implementation and standards institutions. This paper attempts to compare the development in this subject from academic, standards and industry point of views. The results show that there is an enormous difference between academic research and standards and market domains in term of the evolution of scheduling mechanism